Network Analysis of Audit Partner Rotation† - Pittman, Jeffrey; Wang, Lin; Wu, Donghui (Contemporary Accounting Research, 2022)
ABSTRACT Focusing on mandatory partner rotations, we examine the importance of within‐firm network connections to the selection of successor partners and the impact of those connections on post‐rotation audit performance. Using data from China, we track partners' history and identify incumbent‐successor connections stemming from jointly conducted prior engagements. Although these connections can enhance incumbent‐successor information transfers and thus post‐rotation audit performance, they may also pose a threat to quality by compromising the successor's independence. Among the pool of replacement candidates, we find that individuals with stronger connections with the incumbent are more likely to be appointed as successors. This finding is more pronounced when the audit engagement is more complex, client‐specific knowledge is not readily available to the succeeding partner, and the engagement is more valuable to the audit firm. We also document that successor‐incumbent connections are associated with equal or better post‐rotation audit quality and fewer client defections. These results suggest that the benefits of network‐based successor selection may outweigh its costs. By enriching our understanding of the partner transition process, this study contributes to the public policy discourse on partner rotation.